ORIENTASI DAN PENDEKATAN BELAJAR BERBAHASA INGGRIS - Djamaluddin Darwis (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2011)
As a mean of communication, English language becomes very important in this globalization era. The difficulties in learning English as a new language are something that should be overcome. Communicative competence is the major goal for the English learners; it is not based on what to know the language but based on how to use the language. Therefore the competencies in learning English as a new language, is not merely grammar and vocabulary. It is also consist of other competencies that relates to process of communication. A good language learner will have persistence, determination, practice and the development of various social and learning strategies in learning new language, especially English.